Internet 'shellebrity' reflects on origin of rare mirror-image snails. (24th June 2020) - Davison, Angus; Thomas, Philippe; ,
Abstract : While animal bodies are typically bilaterally symmetric on the outside, the internal organs nearly always show an invariant left–right (LR) asymmetry. In comparison, snails are both internally and externally LR asymmetric, outwardly obvious in the shell coiling direction, or chirality. Although some species of snail are naturally variable for chirality, sinistral individuals occur very rarely in most species. The developmental and genetic basis of these rare mirror-imaged individuals remains mysterious. To resolve this issue, the finding of a 'one in a million' sinistral garden snail called 'Jeremy' was used to recruit citizen scientists to find further sinistral snails. These snails were then bred together to understand whether their occurrence is due an inherited condition. The combined evidence shows that rare sinistral garden snails are not usually produced due to a major effect maternal Mendelian locus. Instead, they are likely mainly produced by a developmental accident. This finding has relevance to understanding the common factors that define cellular and organismal LR asymmetry, and the origin of rare reversed individuals in other animal groups that exhibit nearly invariant LR asymmetry.